To determine how many zeros the function \( f(x) = x(x - 1)(2x + 4)^2 \) has, we can break it down into its factors.
- The factor \( x \) provides 1 zero at \( x = 0 \).
- The factor \( (x - 1) \) provides another zero at \( x = 1 \).
- The factor \( (2x + 4)^2 \) is a squared term. The equation \( 2x + 4 = 0 \) gives us: \[ 2x = -4 \implies x = -2. \] Since this factor is squared, it contributes 2 zeros at \( x = -2 \).
Now, let's count the total number of zeros:
- From \( x \): 1 zero
- From \( (x - 1) \): 1 zero
- From \( (2x + 4)^2 \): 2 zeros
Adding these up gives: \[ 1 + 1 + 2 = 4 \text{ zeros}. \]
Thus, the function \( f(x) = x(x - 1)(2x + 4)^2 \) has 4 zeros in total, including repeated zeros.
The response is: 4.